Liogenys Guerin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae: Diplotaxini) of northern South America and Central America: taxonomic overview with four new species - Cherman, Mariana A.; Basílio, Daniel S.; Mise, Kleber M.; Frisch, Johannes; Smith, Andrew B.t.; Almeida, Lúcia M. (Zootaxa, 2021)
The biodiversity of northern South American and Central American Liogenys Guérin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae: Diplotaxini) is reviewed. Four new species are described: L. clipeosetosa Cherman, new species; L. genieri Smith & Cherman, new species; L. granadina Cherman, new species; and L. schneiderae Cherman, new species. The male of L. quadridens (Fabricius, 1798) and the female of L. quadridentata Blanchard, 1851 are described for the first time. Liogenys gebieni Moser, 1921 is a new junior subjective synonym of L. macropelma Bates, 1887. The northernmost record of Liogenys is emended to Trinidad and Tobago for L. granadina Cherman, new species and L. schneiderae new species. Diplotaxis puberea cuprascens (Bates, 1887) new combination, Diplotaxis puberea puberea (Bates, 1887) new combination, and Diplotaxis pubisternis (Bates, 1887) new combination are all transferred from Liogenys to Diplotaxis Kirby, 1837. Lectotypes are designated for Liogenys gebieni Moser, 1921; Melolontha quadridens Fabricius, 1798; and Liogenys quadridentatus Blanchard, 1851. An identification key to northern South American Liogenys is presented.